PEMANFAATAN GULA MERAH DAN AIR KELAPA TERHADAP PERTUMBUHAN AYAM BROILER - Lili Yoris; S Fredriksz (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
The purpose of this research is to find out the effect of using coconut water and palm sugar in drinking water to the growth of broiler. The result of this research could be used as information for the farmers and other users in utilizing coconut water and brown sugar increasing the growth of broiler. This research is an experiment that uses a Complete Random Design with 3 treatments and 5 repetitions which are treatments P0 = Feed + Regular water (Controlled); P1 = Feed + Coconut Water; P2 = Feed + Palm Sugar Water. The variables that are observed are: water consumptions, feed consumptions, weight gain and food conversion. Research result shows that water consumption has an apparent difference, feed consumption has no apparent difference, weight gain shows an apparent difference, and food convection shows apparent difference. Research.result shows that utilizing 1% coconut water and brown sugar for broiler has a good result, despite has not yet shows any effects on the amounts of consumed ration or the ration convection. Based on this research it is suggested, to increase the growth and weight of broiler utilize 1% of brown sugar in the chicken’s drinking water.